Corporate Rescue Strategy for PT. BN Through Leveraged Buyout and Product Diversification - Athayani, Resti; Siahaan, Uke MMP (The Indonesian Journal of Business Administration, 2012)
A high humidity level in Indonesia makes rust or corrosion occurs easily. Rust or corrosion on building construction materials may result in disadvantages both financially and security. Therefore, it appeared iron and steel constructions tool that is coated by zinc and alumunium or galvanized, it aims to extend the life of iron and steel construction. The problem faced by PT BN, as one of the coated steel companies is the running capacity which only reaches 30%. This makes the company must be strive to remain viable. PT BN is in the danger zone when carried an analysis of the company health conditions using the Altman Z Score, and threatened with bankruptcy. The company owners can not afford to sustain the company and facing the choice of whether the company will be liquidated, sold its assets, or sold to another party. After conducted the sell company to the management alternative, the profit is much greater for the owners than two others alternative. After buying PT BN through LBO, the new owner will develop the company by producing galvalum with longer age resistance than galvanized. Financial analysis conducted to determine the feasibility of the proposed investment by looking NPV, Payback Period, IRR and ROI. The results showed a feasible value. Scenario analysis, optimistic, most likely, and pessimistic conducted and the results optimistic and most likely scenarios generated a feasible value. Therefore, PT BN chose to sell the company to the management. Keywords : Altman Z Score, LeveragedÂ Buyout, Feasibility Study Analysis, Scenario Analysis, Monte Carlo Simulation